The Influence of Organizational Support, Leader Member Exchange, And Work Stress on Employee Performance With Employee Engagement as Intervening Variables : Pengaruh Organizational Support, Leader Member Exchange, dan Stres Kerja terhadap Kinerja Karyawan dengan Employee Engagement sebagai Variabel Intervening - Rudy Kurniawan; Rifdah Abadiyah (Academia Open, 2020)
This study aims to determine The Influence of Organizational Support, Leader Member Exchange, And Work Stress on Employee Performance With Employee Engagement as Intervening Variables in PT.XYZ. The population used is production employees of PT.XYZ, amounting to 187 people, and in this study as many as 128 people were sampled. The sampling technique used in this study is simple random sampling. Data collection is carried out through questionnaires. To test the hypothesis used multiple linear regression analysis tools, multiple correlation coefficients (R), coefficient of multiple determination (R2), classic assumption test, F test and t test with the help of SPSS statistical 18.0, as well as validity and reliability tests. The results of this study prove that intrinsic organizational support, leader member exchange, and work stress, influences employee performance. organizational support, leader member exchange, and work stress influences employee engagement, besides that intrinsic organizational support, leader member exchange, and work stress, and employee engagement have a direct and indirect influence on employee performance.